Anybody know how to simplify this algorithm:

(x1,x2) are the coordinates of the object pulling the other object, and (x2,y2) are the coordinates of the object being pulled.

x2 - x1 = x

x / abs(x) = x_sign

x^2 = u

y2 - y1 = y

y / abs(x) = y_sign

y^2 = v

u / (u + v) = u

1 - u = v

sqrt(u) * x_sign + x1 = x2

sqrt(v) * y_sign + y1 = y2

(x1,x2) are the coordinates of the object pulling the other object, and (x2,y2) are the coordinates of the object being pulled.

x2 - x1 = x

x / abs(x) = x_sign

x^2 = u

y2 - y1 = y

y / abs(x) = y_sign

y^2 = v

u / (u + v) = u

1 - u = v

sqrt(u) * x_sign + x1 = x2

sqrt(v) * y_sign + y1 = y2